Prevalence, characteristics and risk factors of suicides in Denpasar from 2014-2016 - Pravinthiran Manokaran; Luh Nyoman Alit Aryani; Ni Ketut Putri Ariani (Intisari Sains Medis, 2018)
Suicide is an important health issue worldwide which is generally on the rise from annually. It has no known pathophysiology; it interlinks psychological, biological, societal and environmental factors. Aim: This study was conducted to identify the prevalence and various variables, such as characteristics, methods and risk factors of attempted and completed suicides. Methods: This is a cross-sectional descriptive study which was conducted in Denpasar from 2014-2016 and the subjects of study are those attempted and died from suicides. Data were collected from resident’s log book and medical records from Psychiatric and Forensic departments in RSUP Sanglah and police reports from Polresta Denpasar. Data collected from Polresta has also included those from Forensic. Results: Age group 15-29 years (121), females (118), married people (82), private sector employees (109), and Balinese (108) have highest numbers of suicide attempts in their respective character groups. Poisoning (145) and problems with a partner (99) are the most typical methods of choice and risk factor respectively among the 176 cases of attempted suicides. Age group 30-49 years (11), males (17), married people (16), private sector employees (16), and Balinese (13) have highest numbers of completed suicides. Hanging (22) and economy crisis (13) are the most prevalent method and risk factor among the 23 cases of completed suicides. Conclusion: Findings of this study show that there were 176 suicide attempts and 23 suicide deaths in Denpasar from 2014-2016.